Gastric cancer prevention targeted on risk assessment: Gastritis OLGA staging. Issue 2 (17th February 2019) - Rugge, Massimo; Sugano, Kentaro; Scarpignato, Carmelo; Sacchi, Diana; Oblitas, Walker Jove; Naccarato, Antonio Giuseppe
Abstract: Gastric cancer (GC) ranks among the most lethal epithelial malignancies, and its striking mortality rate prompts a global prevention strategy. Helicobacter pylori ( H. pylori ) gastritis is the main GC promoter, and the 2014 Global Kyoto conference recognized H. pylori gastritis as a (treatable) infectious disease. It is therefore plausible that any large‐scale intervention for H. pylori eradication would result in cleansing the world of the fifth cause of cancer‐related death. Atrophic gastritis is the cancerization field in which GCs (both intestinal and diffuse histotypes) mainly develop. Discontinuing the inflammatory cascade triggered by H. pylori is tantamount to preventing GC. For patients (still infected or eradicated) who have already developed gastric atrophy, the severity/topography of the atrophic changes correlates with their cancer risk. Gastritis OLGA (Operative Link for Gastritis Assessment) staging consistently ranks the atrophy‐associated cancer risk, providing a solid clinical/biological rationale for establishing patient‐specific surveillance programs. By combining primary and secondary prevention strategies, gastric cancer is a preventable disease.